Verity [large type] - Bergren, Lisa Tawn (The Sugar Baron's daughters, 2019)
"Englishwoman Verity Banning decides to start a business importing horses and other goods the residents of the West Indies need. This trade brings her to New York, where she meets revolutionary Ian McKintrick. When Ian and his Patriot sympathies lay claim to her heart, she'll have to decide for what--and whom--she will fight"--Published by publisher.